An Efficient Synthesis of α, β Unsaturated Ketones via Claisen-schmidt Condensation Reaction using Amino Acid Based Ionic Liquids - Selvaraj, Ganesh G.; Jayaraman, Sakthinarayanan; Selvarasu, Uthayanila; Velumani, Bharathi Priya; Parasuraman, Karthikeyan (Current Catalysis, 2021)
Synthesis of chalcone by Claisen–Schmidt condensation using recyclable L- aspartic acid coupled with imidazolium-based ionic liquid as a green synthetic approach has been developed. Present work offers significant advantages, such as high yield, enhanced reaction speed even at room temperature, catalyst reusability, and the involvement of non-toxic reagents. Background: Chalcones belong to the flavonoid family and possess pharmacological and biological activities, including antibacterial, antifungal, immunosuppressive, and anti-nociceptive properties. Objective: Ionic liquids have emerged as powerful tools for molecular organic solvents. Their wide liquid range, easy recovery, and reusability make them a greener alternative to volatile organic solvents. Thus, in the present work, our objective was to employ them as dual catalysts and solvent systems for the synthesis of chalcone via the CS condensation. Methods: In a typical experiment, benzaldehyde (10 mmol), acetophenone (10 mmol), and 2.5 mol% (L-AAIL) ionic liquid were mixed in a 50 mL round-bottom flask. The reaction was proceeded quickly at room temperature with stirring, and the resulting mixture became a biphasic system with the precipitate at the bottom and the upper phase containing some unreacted substrate which was separated from the catalyst by filtration and decantation. The catalyst was extracted with CH2Cl2 and separated for the next cycle. Results: Claisen–Schmidt condensation accomplished with reasonable to good yields, ranging from 78 to 95% at room temperature in presence of the [L-AAIL], as compared to the traditional route at more than 100°C. Conclusion: [L-AAIL] is found a highly efficient and eco-friendly catalyst for the synthesis of chalcone derivatives at room temperature. [L-AAIL] as a solvent and catalyst will exhibit real advantages by providing a ‘green’ process with a safer operation. Furthermore, short reaction periods, mild reaction conditions, easier separation, and reusability of ionic liquid made this methodology valuable for synthetic organic chemists as well as industry.
Keywords: Claisen–Schmidt reaction. green chemistry